Are All Paraphyllia the Same? - Spirina, Ulyana N.; Voronkova, Tatiana V.; Ignatov, Michael S. (Frontiers in Plant Science, 2020)
Moss paraphyllia, the trichome-like or foliose structures on moss stem surfaces, are usually treated as epidermal outgrowths. However, in some taxa of the moss families Leskeaceae, Neckeraceae, and Amblystegiaceae their distribution along the stem is consistently correlated with parts of the stem surface near branch primordia. In other moss families, Climaciaceae, Hylocomiaceae, and Pseudoleskeaceae the specific paraphyllia-generating epidermal layer produces paraphyllia evenly all along the stem. These results suggest that there are at least two different types of regulation of paraphyllia development; however both of them may be involved in the morphogenesis of paraphyllia in some families, for example in the Thuidiaceae. Exogenous abscisic acid treatment consistently increases the number of paraphyllia of the Leskea-type and it also induces the development of proximal branch leaves that normally do not develop a lamina above the stem surface. This fact supports conclusions regarding the homology of the Leskea-type of paraphyllia with leaves.